Telejornalismo em transformação: as mudanças causadas pelo processo de legitimação dos smartphones nas redações - Vieira, Giovanna Conceição (2020)
The use of smartphones promoted changes in the TV news production routines. Considering this scenario, this research will verify which journalistic practices are transformed with the process of legitimizing smartphones in the telejournals. The methodology is called depth hermeneutics, adressed by John B. Thompson, which is divided into three parts: i) social-historical analysis or a bibliographic review on the theme; ii) formal or discursive analysis, based on the observation of Jornal da Record, Record TV, Jornal da Band, Rede Bandeirantes and Jornal da Cultura, TV Cultura, to identify possible ways of using the smartphone in the production of news programs and, afterwards, conducting interviews with professionals from the selected news programs to provide an overview of the use of the smartphone in the production of news; and finally iii) an interpretation, by the time the survey analyzes how information is collected and verifies the levels of legitimacy that the smartphone exercises within the logic of producing a telejournal. Therefore, an analysis of the process for legitimizing smartphones in telejournals was applied in four categories: i) as a work tool, ii) aesthetic quality, iii) informational relevance and iv) relationship with the audience. As main results, it can be highlighted that the smartphone did not reach a level of full legitimacy in the newsrooms, due the fact that many times, journalists have no autonomy to use the device in the construction of stories. This indicates a lack of legitimacy on behalf of the journalistic institutions, which still concentrates on theirselves the decisions on whether or not to use the smartphone in the television news production process, especially on issues related to the aesthetic quality of the image and the relationship with the audience. However, considering that this process is in constant transformation, it was possible to identify an advanced level of microlegitimations related to smartphones, in which journalists recognizes the device as a tool applied to journalistic practice, changing and facilitating the process of news production, considering both a legitimate work tool and a supplier of important content for the reports.